Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes de primer ciclo de la Carrera de Psicología Clínica de la Facultad de la Salud Humana de la Universidad Nacional de Loja, 2024. - Castillo Granda, Maria Belen (2024)
The purpose of the research was to analyze the basic cognitive process of attention, memory and their relation with the reading comprehension. The study is framed by a quantitative approach of a correlational and transversal type with a no-experimental design. The sample was of 30 first period college students of Clinic Psychology from Universidad Nacional de Loja in 2024. The data were collected with D2 Tests of attention, RIAS memory assessment and the Reading Comprehension Evaluation Instrument for College Students (ICLAU). The correlation between the variables was stablished using Kendall ́s Tau-b correlation coefficient in function of Pearson ́s correlational interpretation. The results showed 60% of the students reached a low level of attention, 30% reached a hig level and 10% a medium level. Regarding memory, 73.3% achieve a high level and 26.7% a medium level, with no results for the bottom level. I nrelation to reading comprehension 53.3% of evaluated was in a medium level and 46.7% high level results. The correlation of attention, memory and the reading comprehension shows a positive relation with an average magnitude between them, with a Pearson ́s lineal correlation between +0.11 and +0.50. This result states that both correlations have adequate levels of attention and memory, showing a better progress in reading comprehension.